Legal Protection of Children in Armed Conflict in the View of International Humanitarian Law - Mangku, Dewa Gede Sudika; Yuliartini, Ni Putu Rai (Universitas Negeri Semarang (UNNES), 2021)
In an armed dispute, the protected persons include combatants and the civilian population. Combatants who have horse de combat status must be protected and respected in all circumstances. Combatants who fell into enemy hands gained the status of prisoners of war. Protection and rights as prisoners of war are regulated in Geneva Convention III of 1949. Meanwhile, civilians are entitled to protection as regulated in Geneva Convention IV of 1949. The legal protection given to children is more focused on the consequences of armed disputes that will affect or affect children. As part of the civilian population, children who do not participate in hostilities receive general protection without any adverse distinction based on ethnicity, nationality, religion, or political opinion, and are intended to alleviate the suffering caused by war